Reform of Gujranwala Water and Sanitation Agency : Design of Institutional Framework and Corporate Structure - Ali Shah, Syed Mansoor (World Bank, Washington, DC, 2013)
WASA-G is an agency established by the Authority under the Punjab Development of Cities Act, 1976 ('PDCA') to 'carry out functions of the authority in relation to development, operation, and maintenance of water supply, sewerage and drainage system within the boundaries of Gujranwala Development Authority (GDA) and to carry out all functions ancillary hereto. Authority means the development authority i.e, GDA created under PDCA. One of the functions of the authority is to establish an agency or agencies and entrust to it such powers and functions as it may deem fit with the approval of the Government. The functions of water supply, sewerage and drainage have been 'entrusted' to WASA-G, an agency of the authority under the PDCA. There is no further detail in PDCA regarding the legal structure of the agency. WASA-G is, therefore, no more than a wing or department of the authority entrusted with a specific function of water supply, sewerage and drainage and matters ancillary thereto and does not enjoy an autonomous legal status. The authority is therefore the service provider (through WASA-G) and the regulator. Further, the authority can give direction to government agencies to execute the scheme, if falling within the jurisdiction of the government agency.